De Memphis à Rome : actes du Ier Colloque international sur les études isiaques, Poitiers-- Futuroscope, 8-10 avril 1999 - Bricault, Laurent. (Religions in the Graeco-Roman World, 2000)
The studies of the Isiac Cults are forty years old. Many of the scholars who have contributed to the development of this particular field of research, - the diffusion of the Egyptian cults in the Graeco-Roman world -, met in the Futuroscope of Poitiers for a three-day colloquium, to establish the progress of research, and the subjects which need more discussion. The synthesis of this colloquium is presented in this volume. The best specialists in the world give their assessment of the past forty years of research: which tools do students and scholars have? Which -provisional- conclusions can be drawn about, for example, the hellenization of Isis, the reality of the Roman soldier's devotion to Isis or Sarapis, the celebration of the Isiaca in Rome from Republican days well into the Empire? This volume is a very useful update on what we do and do not know in the study of the Isiac cults in the Graeco-Roman world.